Predictors of long term survival after surgical resection in carcinoma gall bladder - Vivek Gupta; Saket Dr Saket Kumar; Rahul Rahul; Abhijit Chandra (International Journal of Medical Research and Review, 2016)
Background-Carcinoma of the gallbladder is known to be associated with a dismal prognosis, with majority of patients presenting at late stages. Controversies still exist regarding the optimal management and the extent of surgery.Methods-This study was done at a tertiary hospital in an endemic region for cancer gallbladder (north Indian Gangetic belt). All patients operated for cancer gallbladder between January 2006 and January 2011 were included, with details of clinical presentation, survival analysis and identification of prognostic factors.Results- Of the total 252 patients of carcinoma gall bladder identified during the study period, 71 patients were explored surgically. Curative resection was achieved in 27 patients with 10 long term survivors (disease free interval >3years). Nodal status, TNM stage and bilirubin levels affect survival. Majority of patients presented late in the course of disease (Mean of 44 days from the onset of symptoms).Conclusion-Majority patients with carcinoma gallbladder in our region have advanced unresectable disease. Bilirubin levels at presentation predict resectability. Nodal involvement implies a worse prognosis; however the extent of lymphadenectomy to be done is still debatable. Community screening programs and sensitization of local physicians for early referral can improve survival in endemic areas.